リュツォ・ホルム ワン ノ カイヒョウ ノ トクセイ ト セイチョウ カテイ - 河村, 俊行; カワムラ, トシユキ; 滝沢, 隆俊; タキザワ, タカトシ; 大島, 慶一郎; オオシマ, ケイイチロウ; 牛尾, 収輝; ウシオ, シュウキ; Kawamura, Toshiyuki; Takizawa, Takatoshi; Ohshima, Kay. I.; Ushio, Shuki (1997)
P(論文) 海氷の特性と成長過程を解明するための観測がリュツォ・ホルム湾の定着氷で1990年から1991年の2年間にわたって行われた。湾内の積雪深は沖合いの観測点で, 冬季に1.0から1.5mと非常に厚くなった。積雪深と氷厚の観測から, 多雪域の海氷は冬にはほとんど成長しないにもかかわらず, 夏には非常に厚くなることが確認された。海氷の構造・塩分・酸素同位体比の結果から, この海氷は通常の成長とは異なり, 海氷の表面で上方に成長していることが分かった。その上方成長は雪ごおりと上積氷の形成により起こっていると結論された。南極の海氷での上積氷の形成は以前に報告されていない。上積氷の生成条件である積雪の融解の証拠も得られた。この様な夏の上方成長は少雪域の海氷では見られなかった。従って, 積雪は海氷の成長過程と構造に多大な影響を及ぼす。この報告の前半で, 海氷の一般的な構造や南極域での海氷の特性が述べられている。 Observations of multiyear land fast sea ice were made in Lutzow-Holm Bay, Antarctica over a period of two years from 1990 to 1991 to determine the snow and ice characteristics and ice growth prowth processes. The snow depth in the bay reached remarkably high values of 1.0 to 1.5m during the winter season at offshore stations. From analysis of ice thickness measurements, it is confirmed that fast ice with deep snow cover shows little growth during winter but substantially thickens during the summer months. On the basis of ice core structure, salinity and stable isotopic composition, it is concluded that the sea ice grows not downward as in ordinary growth but upward at the top of the sea ice. It is also concluded that the upward growth is caused by snow ice and superimposed ice formation. Superimposed ice formation on sea ice in Antarctica has not been reported previously. Evidence for snow cover melting, which is a prerequisite for superimposed ice formation, was also found. The summer upward growth was not found in sea ice with low snow accumulation. Snow cover, therefore, significantly affects the growth processes and structure of sea ice. General sea ice structure and characteristics of Antarctic sea ice are reviewed at the beginning of this report. departmental bulletin paper